HCV Infection in the Republic of Sakha (Yakutia) and Its Role of Genotypes in Clinical Outcomes of the Disease - V. K. Semenova; S. S. Sleptsova; S. I. Malov; E. D. Savilov; S. I. Semenov; I. V. Malov; L. A. Stepanenko; O. B. Ogarkov (Acta Biomedica Scientifica, 2020)
Aim of the research. To study the epidemic manifestations of HCV infection in the Republic of Sakha (Yakutia) in order to develop recommendations for improving the effectiveness and quality of treatment and prevention measures. Materials and methods. The paper uses materials from the official statistics of the Territorial Department of Rospotrebnadzor of the Republic of Sakha (Yakutia) for 1994–2018, and data from the electronic register «Chronic viral hepatitis in the RS (Ya)» (2019). Molecular and biological studies of the genotype of the hepatitis C virus were performed jointly on the basis of the Federal state budgetary Institution «Central research Institute of epidemiology» of Rospotrebnadzor (2007–2011, n = 75). To assess the epidemiological situation, the rate of increase in morbidity is calculated on the basis of data equalized by the method of least squares. Statistical processing was performed using the SPSS 17 program. The critical significance level is assumed to be 0.05. Results. Thus, the study of long-term dynamics of the incidence of viral hepatitis shows that in the Republic of Sakha (Yakutia) a consistently high level of incidence of HCV with adverse trends in the development of the epidemic process remains. Analysis of the distribution of different variants of HCV genotypes allowed us to establish the prevalence of genotype 1b, which can determine the high frequency of cirrhosis and primary liver cancer. The current situation in the Republic regarding the incidence of viral hepatitis requires detailed monitoring, improvement of epidemiological surveillance and introduction of modern treatment methods. It is also necessary to improve the quality of health education among the population of the Republic.